Extremely fast increase in the organic loading rate during the co-digestion of rapeseed oil and sewage sludge in a CSTR--characterization of granules formed due to CaO addition to maintain process stability - Kasina, M (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
In a co-digestion system running with rapeseed oil and sewage sludge, an extremely fast increase in the organic loading rate was studied to develop a procedure to allow for flexible and demand-driven energy production. The over-acidification of the digestate was successfully prevented by calcium oxide dosage, which resulted in granule formation. Mineralogical analyses revealed that the granules were composed of insoluble salts of long chain fatty acids and calcium and had a porous structure. Long chain fatty acids and calcium formed the outer cover of granules and offered interfaces on the inside thereby enhancing the growth of biofilms. With granule size and age, the pore size increased and indicated degradation of granular interfaces. A stable biogas production up to the organic loading rate of 10.4 kg volatile solids m(-3) d(-1) was achieved although the hydrogen concentration was not favorable for propionic acid degradation. However, at higher organic loading rates, unbalanced granule formation and degradation were observed. Obviously, the adaption time for biofilm growth was too short to maintain the balance, thereby resulting in a low methane yield